What is the most effective nonsurgical medical treatment for adults with mild to moderate ulcerative colitis?. Issue 1 (January 2018) - Joyce, Daniel; Eskander, Happy; Alwazni, Montadher; Lukose, Anson
Abstract : EVIDENCE‐BASED ANSWER : Oral 5‐aminosalicylic acid (5‐ASA) formulations such as mesalamine produce similar remission rates as oral sulfasalazine (SASP) with fewer side effects (SOR: A, meta‐analysis of RCTs). Mesalamine enemas are more effective than budesonide enemas with fewer side effects (SOR: B, single RCT). Combination therapy with rectal and oral mesalamine is more effective than oral mesalamine alone (SOR: B, single RCT).